Short Communication. Effect of phosphorus nutrition and grain position within maize cob on grain phosphorus accumulation - Nadeem, Muhamamad; Mollier, Alain; Vives, Alain; Prud´HommeLoic; Niollet, Sylvie; Pellerin, Sylvain (Spanish Journal of Agricultural Research, 2014)
Nutritional status of grains may vary due to external nutrient supply and their position within parent maize cob. Phosphorus (P) is the least mobile nutrient in the soil and therefore newly growing seedlings are largely dependent on the stored grain P contents which are accumulated during the crop maturity period. Objective of this study was to access the effects of different P applications and grain positions on P and dry matter contents in grains. Phosphorus application and grain position has significant (p<0.05) effects on P contents in grains whereas dry weight and P content are highly correlated. Grain weight and P contents decreased linearly from base to apical position possibly due to flow of nutrients from base towards apical position within cob. Significantly higher grain dry weight (0.35±0.01 g) and P contents (962±57 µg P) are recorded in high P application (92.50 kg ha-1) rate on base position whereas minimum grain dry weight (0.14±0.01 g) and P contents (219±11 µg P) were recorded on apical grain position in low P application (5.60 kg ha-1) rate. The results suggest that for better seedling P nutrition especially in soils of low inherent P, maize grains should be selected from base or middle position where maximum dry weight and P contents are concentrated to support the seedlings to reach at growth at which roots are capable of external P uptake.